Angular Momentum of Stars and their Planets. (10th December 2018) - Gurumath, Shashanka R.; Hiremath, K. M.; Ramasubramanian, V.
Abstract: To understand the distribution of angular momenta between host stars and their planets, we estimate the spin angular momentum ( J spin ) of host stars that follow a power law 10 ( 42.33 ± 5.40 ) M ⋆ M ⊙ ( 4.18 ± 0.53 ) with stellar mass M ⋆ M ⊙ . Similarly, the orbital angular momenta ( L p ) of exoplanets are estimated, and the best fit yields a power law, 10 ( 42.66 ± 1.79 ) M p M J ( 1.26 ± 0.05 ), with the exoplanetary mass M p M J . Furthermore, the total (spin and orbital) angular momentum J tot of the stellar planetary system is computed, and a power law of the form J tot  =  10 ( 43.11 ± 6.82 ) M p M J ( 0.94 ± 0.14 ) is obtained. In addition, an analysis between specific angular momenta ( I p ) of planets and planetary masses reveals that specific angular momentum is nonlinearly related with planetary mass in case of multiplanetary systems and is independent of planetary mass in case of single-planetary systems. We find that the probability of detecting Earth-like planets is more likely for host stars that have total angular momentum ≤10 41 kg m 2 s −1 . Finally, a power-law relationship is obtained between exoplanetary masses and their orbital distances in case of multiplanetary systems and, is independent in case of single-planetary systems.